A comparative analysis on water quality in an urban micro watershed - Zambrano, Karen Tavares [UNESP]; Poleto, Cristiano; Oliveira, Jefferson Nascimento [UNESP] (Emerald, 2017)
Purpose: This study presents a comparative analysis of water quality data in an urban micro watershed to study the magnitude of impacts on the water quality parameters over the last decade. The purpose of this paper is to evaluate the degree of deterioration using the water quality index. Design/methodology/approach: Rapid urban growth without proper land use and occupation planning results in the overload of urban water resources. Therefore, a literature review was conducted on the research subject published in the dissertation databases of the Engineering Faculty of Ilha Solteira, which resulted in the selection of two dissertations on water quality in the Ipê Stream, Ilha Solteira – SP, Brazil. The results will be evaluated according to the Brazilian laws and regulations in force. Findings: This study shows that pollution and degradation in the stream intensified during the study period, with the most impacted areas within the urban perimeter. Practical implications: The increasing impacts underscore the need for efficient measures such as implementation of retention reservoirs, elimination of clandestine sewage connections and restoration of riparian forests. Originality/value: This study highlights the need to monitor the water quality of streams in order to establish preventive and mitigating measures to avert the growing environmental impacts and to ensure quality water for future generations.
Keywords: Brazil; Literature review; Micro watershed; Water quality